Effectiveness Of Health Education Through Video And Leaflets On Knowledge And Waste Sorting Behavior Among Elementary School Students: A Quasi-Experimental Study - Bustomi, Sadya; Sulistiana, Della (Chakra Brahmanda Lentera Institute, 2025)
Background: Waste sorting has not been widely understood or implemented among elementary school students, resulting in poor waste management in the school environment. However, evidence comparing the effectiveness of video-based versus leaflet-based health education interventions in elementary school settings remains limited. This study aimed to determine the effectiveness of health education on waste sorting on students' knowledge and behavior in State Elementary Schools. Methods: This quantitative study employed a quasi-experimental two-group pretest–posttest design with no control group, following the TREND reporting guidelines. The sample comprised 60 grade V students (30 from SDN Panggung Rawi and 30 from SDN Sukmajaya 1), selected through a total sampling method. Inclusion criteria were active enrollment as grade V students, ability to read and write, and provision of parental consent, while absent students were excluded at the time of data collection. SDN stands for Sekolah Dasar Negeri, which means State Elementary School (public primary school) in Indonesia. Data were collected using a 16-item, expert-validated questionnaire and tested for reliability (Cronbach’s alpha = 0.82 for knowledge and 0.79 for behavior). Univariate analysis used median values, while bivariate analysis applied paired t-tests/Wilcoxon signed-rank tests and independent t-tests/Mann–Whitney U tests, with effect sizes reported as Cohen’s d. Results: At α = 0.05, there was a significant difference in knowledge between the video and leaflet groups (p = 0.012; Cohen’s d = 0.54, medium effect). Similarly, there was a significant difference in behavior change between the video and leaflet groups (p = 0.001; Cohen’s d = 0.71, large effect). No participants dropped out, and complete data were obtained from all respondents.. Conclusion: Health education through videos was more effective than leaflets in improving elementary school students' knowledge and behavior regarding waste sorting. Waste sorting interventions can be effectively integrated into school-based waste management programs.